Physical and hardness performance at different surfaces for titanium alloy (Ti6Al4V) printed using selective laser melting process (SLM) - Farhana Mohd Foudzi,; Lai, Yu Hung; Fathin Iliana Jamhari,; Minhalina Ahmad Buhairi,; Abu Bakar Sulong,; Norhamidi Muhamad,; Nabilah Afiqah Mohd Radzuan,; Izhar Aziz,; Kim, Seah Tan (Penerbit Universiti Kebangsaan Malaysia, 2024)
Selective laser melting (SLM) 3D product is capable of producing varied surfaces such as top, core and bottom surface depending on the product dimensions and building orientation. Each surface may have differences in physical and mechanical properties such as surface roughness, microhardness, and microstructure. Therefore, this study examined the effects of SLM processing parameters as well as volumetric energy density (VED) on surface roughness, microhardness and microstructure on different 3D product surfaces. In this study, a sample of titanium alloy cube (Ti6Al4V) with different surfaces of up skin 1 (US1), up skin 2 (US2), core skin (CS) and down skin (DS) are printed on a 30° building orientation printed through the SLM process. There are nine sets of parameters printed based on the Taguchi experimental design method. All printed cube samples were heat treated to remove the residual stresses generated during the printing process. The effect of processing parameters on micro hardness as well as microstructure on each surface has been studied. This study found that SLM printed Ti6Al4V produced almost identical surface quality for different surfaces of the cubic samples. Surface roughness of US2 ranging between 15.38 μm and 26.22 μm, while DS is slightly rougher with surface roughness in the range of 16.05 μm and 27.64 μm. Microhardness in the nine processing sets however was found to have a bigger difference in values of 387 ± 10 HV (US2) and 362 ± 10 HV (DS). In general, US2 surfaces were found to have high microhardness compared to the DS surfaces due to the formation of long, straight needle-like martensitic microstructure.